سائنٹولوجی کے عقائد کا اسلام و مسیحیت سے تقابلی مطالعہ - Umer Yousaf (الآفاق اسلامی و تحقیقی مجلہ, 2023)
This comparative study delves into the fundamental beliefs and doctrines of three distinct religious systems: Scientology, Islam, and Christianity. Each of these belief systems occupies a unique place within the religious landscape, and this research aims to shed light on their core tenets, practices, and theologies. By examining the historical contexts, sacred texts, and key teachings of Scientology, Islam, and Christianity, this study seeks to identify both commonalities and disparities, offering insights into the ways in which these religions shape the lives and worldviews of their adherents. Through a comprehensive exploration of these faiths, we aim to foster a deeper understanding of their beliefs, rituals, and the impact they have on the lives of their followers. This research contributes to the broader discourse on comparative religion, fostering dialogue and promoting tolerance among diverse religious communities